Impact of creatinine production on the agreement between glomerular filtration rate estimates using cystatin C-derived, and 4- and 6-variable Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations - Hermida-Cadahia, Esperanza F.; Lampon, Natalia; Tutor, J. Carlos (Upsala journal of medical sciences, 2012)
Abstract Background. It has recently been reported that patient selection has a strong impact on the agreement between glomerular filtration rate (GFR) estimates from serum cystatin C and creatinine. The aim of our study was to evaluate the effect of creatinine production rate (CPR) on this subject. Material and methods. GFR was estimated from serum cystatin C and from creatinine using the 4- and 6-variable Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations in 50 healthy subjects, 43 patients with renal failure, 794 kidney and 104 liver transplant recipients, 61 patients with heart failure, 59 patients with biliary obstruction, and 113 critically ill patients. Results. In the 295 patients with impaired CPR (< 900 mg/24 h/1.73 m2), discordances of more than 40% between GFRMDRD4 and GFRcystatinC were observed in 38% of cases, between GFRMDRD6 and GFRcystatinC in 22%, and between GFRCKD-EPI and GFRcystatinC in 27% (in all cases due to GFR overestimation from creatinine). In the 929 patients with maintained CPR (> 900 mg/24 h/1.73 m2), greater discordances than 40% between GFRMDRD4 and GFRcystatinC were observed in 8% of cases, between GFRMDRD6 and GFRcystatinC in 9%, and between GFRCKD-EPI and GFRcystatinC in 7% (in the major part of cases due to GFR overestimation from cystatin C). Conclusion. The main source of differences of more than 40% between GFR estimates from serum creatinine and cystatin C is a GFR overestimation in patients with low CPR and GFR underestimation in patients with high CPR by the creatinine-derived equations.